2017
DOI: 10.1659/mrd-journal-d-17-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Migration and Livelihood Resilience in the Face of Climate Change in Nepal

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Recent research findings confirm that water-induced hazards are the key driver of labor migration for nearly 80% household in the Nepalese Himalayas (Banerjee et al, 2011;Gautam, 2017), having a negative effect on both the migrants and the populations left behind. Studies in other parts of Nepal have found that migration has a negative effect on agriculture in the form of labor shortages and land abandonment (Adhikari and Hobley, 2011).…”
Section: Decision-making Process Unfolded -Challenges Of Outmigrationmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent research findings confirm that water-induced hazards are the key driver of labor migration for nearly 80% household in the Nepalese Himalayas (Banerjee et al, 2011;Gautam, 2017), having a negative effect on both the migrants and the populations left behind. Studies in other parts of Nepal have found that migration has a negative effect on agriculture in the form of labor shortages and land abandonment (Adhikari and Hobley, 2011).…”
Section: Decision-making Process Unfolded -Challenges Of Outmigrationmentioning
confidence: 78%
“…Distorted family life, shortage of labor in the village and exacerbated inequalities are among the key drivers of social disintegration and further impoverishment (Chapagain and Gentle, 2015;Jaquet et al, 2016;Sapkota et al, 2016). Labor migrants are also not likely to be better off themselves, because they lack the social ties, education, and resources required to overcome the administrative and monetary constraints on the way to better and more secure jobs (Gautam, 2017).…”
Section: Decision-making Process Unfolded -Challenges Of Outmigrationmentioning
confidence: 99%
“…Overall, the study stresses the need for a deeper understanding of the role of translocal livelihood diversification for food security. While translocality has become an increasingly well-described phenomenon over the past years, it is necessary to acknowledge how it significantly changes rural livelihoods (Zoomers et al 2016) also in mountain regions (Kreutzmann 2012;Benz 2014;Gautam 2017). Findings from Ladakh depict typical processes, which have also been described for other areas within the Hindu Kush, Karakoram, and Himalayan region (Rasul et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Taking a broader perspective on food systems, it investigates how various developments have reshaped local production and consumption patterns in recent decades and how this has affected food security, defined as the outcome of a resilient food system. Compared to other parts of the Hindu Kush-Himalayan region (eg Tiwari and Joshi 2012;Dame 2015;Hussain et al 2016;Gautam 2017), few empirical studies on food systems in northern Pakistan exist (Dittrich 1997(Dittrich , 1998Herbers 1998), making it a particularly relevant study region.…”
Section: Introductionmentioning
confidence: 99%